Hubungan Usia dengan Kesehatan Mental Ibu hamil Kecamatan Bantul - Ayu Hapsari, Rani; Zuliyati, Isti Chana; Lestari, Prasetya; Margiati, Margiati (Pustaka Galeri Mandiri, 2025)
Maternal age is one of the factors that can affect a woman's mental health while she is pregnant. As a woman gets older, it can have an impact on both her body and mind, including during pregnancy. Depression is one of the main health problems around the world. Many pregnant women experience anxiety because of the physical, hormonal, and emotional changes that happen during pregnancy. Stress during pregnancy often comes from the physical changes, changes in hormones, and emotional challenges that happen as the baby grows. This study aimed to look at how a woman's age relates to her mental health during pregnancy in Bantul District. The study used a descriptive analysis with a cross-sectional approach and included 83 pregnant women as the total group. The sample size was determined using Slovin's formula, which led to 45 participants. Information was gathered using the DASS-21 questionnaire, and a univariate analysis was done to look at how often different things happened. The results showed that there is a significant connection between a woman's age and her mental health during pregnancy in Bantul District, as shown by a p-value less than 0.05. This means that a woman's age is an important thing to consider when checking her mental health during pregnancy. Healthcare workers should be especially careful about the mental health of pregnant women, especially younger mothers. They should offer help like counseling, education, and support to help reduce stress and prepare women better for pregnancy and childbirth.